Implementasi Model Pembelajaran VAK (Visual Auditorial Kinestetik) dalam Mengembangkan Efikasi Diri Siswa Kelas VII - Fitriyani, Nur; Hidayat, Sholeh; Rusdiyani, Isti (Universitas Mathla'ul Anwar Banten, 2023)
In the world of education, there is a need for an appropriate learning model to support student success, some of the obstacles experienced by teachers and students. This makes a significant change in the learning system used. The VAK learning model (Visual, Auditory and Kinesthetic) can stimulate students' self- efficacy in the subject of interaction between living things. This study aims to analyze the implementation of the VAK VAK learning model (Visual Auditorial and Kinesthetic) in developing the self-efficacy dimensions of class VII students at SMPN 1 Waringinkurung by using a qualitative approach with a descriptive method. The process of collecting data is done by using interviews, observation and documentation. The results of the study found that the dimensions of student self-efficacy were stated in the good category, with a total of six respondents based on field notes, interview notes and observations. In this category each student has different characteristics in each dimension of efficacy starting from magnitude, strength and generallity. In implementing the VAK learning model (Visual, Auditory and Kinesthetic) it gives quite good results because it is able to make learning more varied and not monotonous so that it is much liked by students. Even though in this case there are still many obstacles to be overcome during learning, the teacher can overcome them little by little well. Factors supporting the implementation of the VAK learning model (Visual, Auditory and Kinesthetic) include teachers, technology.